Pengaruh Self Efficacy, Motivation Work Behaviour, dan Work Engagement Terhadap Kinerja Karyawan pada Usaha Sarung Tangan Rajut UD Tiga Putri - Mirnanda Wahyu Prastika; Sumartik; Dewi Andriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of self efficacy, motivation work behavior, and work engagement on the performance of UD Tiga Putri employees. This study uses quantitative research methods with non-probability sampling methods and total sampling techniques, where the population is all production employees at UD Tiga Putri so that the sample in this study is equal to the total population of 102 respondents. Data collection techniques using questionnaires. Data analysis techniques used in this study include validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression tests, t tests, and f tests with SPSS (Statistical Package for the Social Sciences) tools 25th version. The results of this study prove that self efficacy, motivation work behavior, and work engagement affect the performance of UD Tiga Putri employees both partially and simultaneously.